Robotic mechanical design for brick-laying automation. Issue 1 (1st January 2017) - Dakhli, Zakaria; Lafhaj, Zoubeir
Abstract: This paper investigates the potential for automation of masonry work. A brick-laying robot was designed and the robot's design criteria were such that it should be able to construct a wall using cinder blocks autonomously. The paper outlines considerations for the entire process of implementing the robot, from material input and stock management to construction process by the robot itself. The design included the functioning of the brick-laying robot's head. Finally, comparisons were made in terms of cost and time efficiency between the robot and traditional methods for masonry assembly. The results revealed that the designed robot optimized time and cost deliverables with a noticeable waste reduction and an increase in productivity.